THE EFFECT OF CORRIDOR BOGOR - SUKABUMI INTER-URBAN TRANSPORTATION ON REGIONAL DEVELOPMENT: A CASE CIGOMBONG DISTRICT, BOGOR REGENCY, WEST JAVA, INDONESIA - Kasikoen, Ken Martina (Department of Urban and Regional Planning, Diponegoro University, 2017)
Inter-urban transportation which connects cities has significant impacts to the regional development of the surrounding area. Regional development used to be measured by its economic development, population growth, availability of living supporting facilities, and land use change. These variables may also be used to measure the regional development impact by the availability of inter-urban transportation. Cigombong District in Bogor Regency has a very strategic location due to it passed through by various inter-urban transportation routes namely railway (Pangrango Train) with a station (Cigombong Station) and regional roads (state and provincial roads) connecting Bogor City and Sukabumi City. The plan to construct the Bocimi (Bogor-Ciawi-Sukabumi) toll road which will pass through with exit gate located in this district is predicted to push the regional development in this district even further. This study aimed to understand the regional development in Cigombong District impacted by the availability of inter-urban transportation. This research used method of the population growth, Weighted Centrality Index (WCI). of available facilities, and the land use change. Results of this research show that high growth rate of population, rapid development of facilities centers, and rapid change of land use from green area become residential area took place in the area surrounding inter-urban transportation routes (road network as well as train station) namely Cigombong, Tugu Jaya, Ciburuy and Ciburayut Villages. It can be concluded that the development of Corridor Bogor-Sukabumi inter-urban transportation had effect on regional development that can be identified by population growth, residential facilities centers, and land use change. In turn, it can be used by the local government as one the input for formulating policy for enhancing resilience of the region.